PCV2 Triggers PK-15 Cell Apoptosis Through the PLC–IP3R–Ca2+ Signaling Pathway - Wang, Shuo; Li, Chen; Sun, Panpan; Shi, Jianli; Wu, Xiaoyan; Liu, Chang; Peng, Zhe; Han, Hong; Xu, Shaojian; Yang, Ying; Tian, Yao; Li, Jiaxin; et al. (Frontiers in Microbiology, 2021)
Phospholipase C (PLC) is a key enzyme in the cell membrane. PLC hydrolyses phosphatidylinositol 4,5-bisphosphate (PIP2) to generateinositol 1,4, 5-triphosphate (IP3) and diacylglycerol (DAG) that regulates a variety of cellular processes. Evidence indicates the pivotal role of PLC and inositol 1,4,5-trisphosphate receptor (IP3R) in influencing Ca2+ release from the endoplasmic reticulum (ER). At the same time, the imbalance of Ca2+ will stimulate endoplasmic reticulum stress (ERS), leading to cell apoptosis.Viral infection could triggers host defense through apoptosis of the infected cells. However, it is not clear how porcine circovirus type 2 (PCV2) induces apoptosis by affecting Ca2+ homeostasis. We show here that PCV2 infection induces the increased cytoplasmic Ca2+ level and apoptosis. We also found that the ER swelling of PK-15 cells after viral infection by transmission electron microscopy. Further more, the activation of PLC-IP3R-Ca2+ signaling enhanced apoptosis in infected PK-15 cells.Taken together,our findings suggest that PCV2 infection trigger ERS of PK-15 cells via the PLC-IP3R-Ca2+ signaling pathway to promoted the release of intracellular Ca2+, and led to cell apoptosis.